Novels, Readers, and Reviewers Responses to Fiction in Antebellum America - Baym, Nina (Cornell University Press, 2018)
This book describes and characterizes responses of American readers to fiction in the generation before the Civil War. It is based on close examination of the reviews of all novels-both American and European-that appeared in major American periodicals during the years 1840-1860, a period in which magazines, novels, and novel reviews all proliferated. Nina Baym makes uses of the reviews to gain information about the formal, aesthetic, and moral expectations of reviewers. Her major conclusion is that the accepted view about the American novel before the Civil War-the view that the atmosphere in America was hostile to fiction-is a myth. There is compelling evidence, she shows, for the existence of a veritable novel industry and, concomitantly, a vast audience for fiction in the 1840s and 1850s.